Thermal performance enhancement of laminar flow using compound twisted square duct and variable pitch twisted tape inserts - V.P. Chithra; V. Jayakumar; Balaji Bakthavatchalam; Sambhaji Kashinath Kusekar; Kashif Irshad; Khairul Habib (Case Studies in Thermal Engineering)
This study involves a computational analysis to find the effectiveness of incorporating twisted tape within a twisted square duct for improving heat transfer, focusing on laminar single-phase flow. The primary goal is to study how varying the tape pitch (y) influences the hydrothermal performance of this system. The twisted square duct pitch (S) and twist ratio (H) were kept constant. The numerical analysis is performed under conditions of uniform wall temperature, and varying the pitch ratio (y/S) across values of 0.25, 0.5,0.75, 1, 1.25, 1.5 and 1.75. The obtained findings suggest that the addition of twisted tape within the twisted square duct results in a greater rate of heat exchange and pressure drop relative to the simple twisted square duct. Research reveals that despite a higher rate of heat transfer for a pitch ratio of 0.25 the increased friction factor results in less effective thermal performance compared to the cases with pitch ratios of 0.75 and 0.5. The thermal performance factor reaches its peak at 1.32, corresponding to the Reynolds number 1000 for a pitch ratio of 0.75 case. Conversely, the lowest thermal performance factor value of 0.89 is observed at the Reynolds number 500 for pitch ratio 1.25 case.